Non-enzymatic sensing of carbohydrates using a nickel–chromium alloy electrode - Pissinis, Diego Ezequiel (2013)
A highly sensitive non-enzymatic carbohydrates sensor based on a nickel hydroxide film on a nickel alloy electrode was developed. The electro-catalytic film is formed by using a potential scan program developed in our research group. This program facilitated the formation of stable proportions of Ni(II)/Ni(III) oxy-hydroxides which are necessary for the electro-catalysis. The structural morphology and roughness of the oxy-hydroxides were characterized by using scanning electron microscopy and atomic force microscopy. The electrochemical behavior of the electrodes in 0.10 M NaOH and in the presence of carbohydrates was characterized by cyclic voltammetry and chronoamperometry, showing good catalytic activity for the anodic oxidation of carbohydrates. Fast and significant amperometric responses were obtained with the renewable nickel hydroxide films, which were easily constructed on the electrodes’ surfaces by potential cycling. The good analytical performance, low cost and straightforward preparation method make this alloy a promising electrode for the development of effective non-enzymatic carbohydrates sensor.